Analysis of images, social networks and texts : 5th International Conference, AIST 2016, Yekaterinburg, Russia, April 7-9, 2016, Revised selected papers /: 5th International Conference, AIST 2016, Yekaterinburg, Russia, April 7-9, 2016, Revised selected papers. (2017) - Unknown
No abstract available